When the trees go what then ? - Jambawai, Sam Musa (Technical Centre for Agricultural and Rural Cooperation, 1989)
When the trees go what then ?Sam Musa Jambawai Sam Musa- Jambawa has been a professionsl forester for over 20 yearse before being appointed Programme of Officer for the Conservation Society of Sierra Leone. One of Sierra Leone's major problems is...